Collection of Manuscripts of the Archbishop Neil (Isakovich) (1838–1853) of Irkutsk, Nerchinsk and Yakut: the Results of the Study in the XIX–XXI Centuries - N. K. Chernyshova (Библиосфера)
This article is devoted to one of the largest handwritten collection of Siberian manuscripts belonging to Archbishop Neil (Isakovich) of Irkutsk, Nerchinsk and Yakutsk (30–50s XIX century). The purpose of the work is to examine the history of its study in the context of the development of source science and the formation of archaeography in Russia during this period, the characteristics of the collection and the disclosure of source and historiographical the meanings of the collected documents and manuscripts. The collection of Archbishop Neil is kept in the book and archive archives of the city of Yaroslavl – the State Archive of the Yaroslavl Region (GAYAO) and the Yaroslavl Historical, Architectural and Art MuseumReserve (YAMZ). The stages of studying the collection by representatives of the cultural and scientific community of Russia are highlighted. The works of pre-revolutionary and Soviet scribes of Siberia depict the process of formation of the collection, the ways the archbishop works with documents and manuscripts, mentioned the areas of interest of the collector and the most interesting manuscripts of his collection. In the middle of the XX century, the famous Yaroslavl archeographer V. V. Lukyanov carried out a scientific description of the meeting of Archbishop Nile. It was included in the descriptions of the collections of the archives where it is currently located, and published. Finally, in 2019, Yaroslavl archivists, on the initiative of Irkutsk archeographers T. A. Kryuchkova and S. V. Melnikova, digitized part of the manuscript collection of Archbishop Nile stored in the GAYAO, which made it possible to present the manuscript collection of the archbishop to the scientific community of Siberia and not only Siberia. Electronic edition of the ”Treasures of the Archive of Archbishop Neil (N. F. Isakovich)”, supplemented by ”An overview of the documents of the personal collection of Archbishop Neil (N. F. Isakovich) from the State Archive of the Yaroslavl region”, testifies to the source value of the collection and individual striking monuments, allows you to clarify the composition of the manuscripts distributed in the region.